Using the Moodle to support effective teaching and learning of math - Zuhrieh Shanaa, Nuha Hamada, Rene Y. Paquibut, (Opción, 2019)
This paper focuses on the use and benefits of the Moodle in teaching and learning math for business at Al Ain University. This research used both quantitative and qualitative methods. As a result, the teachers unanimously considered that the use of the Moodle made teaching math for business easy and interesting compared to the traditional method, which affirms the students’ attitude towards the platform. In conclusion, the positive attitude of both teachers and students in using the Moodle is an indication of the potential success of future effort to optimize the use of its functions.